KEMAMPUAN LITERASI LINGKUNGAN PADA MAHASISWA PENDIDIKAN GEOGRAFI UPGRI PONTIANAK TA. 2024/2025 - Rika Anggela; Rina Rina (STKIP Singkawang, 2025)
Geography education plays a crucial role in the learning process as it enables students to investigate environmental events and issues, fostering a deeper understanding of the environment. To achieve this, Environmental Literacy (EL) skills are essential, allowing students to comprehend and respond to environmental challenges effectively. Therefore, this study aims to assess the environmental literacy levels of Geography Education students across three key components: Cognitive, Affective, and Behavioral.This research employs a survey method with a quantitative approach. The study population consists of Geography Education students at PGRI Pontianak University. The sampling technique used is Total Sampling, encompassing all students from the 2023, 2022, and 2021 cohorts, totaling 110 students. The research instrument includes a questionnaire to assess the Affective and Behavioral components, comprising a series of statements measured using a Likert Scale. Meanwhile, a multiple-choice test is used to evaluate the Cognitive component. The data analysis is conducted quantitatively by calculating the percentage of sub-indicators for the three Environmental Literacy components. Interval Class analysis is then applied to determine the corresponding criteria. The results of the study indicate that the average score obtained by students in the cognitive aspect is 82.2, which falls within the Good category. The affective aspect yielded an average score of 95.87, categorized as Very Good. Meanwhile, the average score for environmental literacy in the behavioral aspect is 87.83, also classified as Very Good.